Kapasitas Administratif dan Efektivitas Transfer Tunai Bersyarat: Bukti dari Tata Kelola Perlindungan Sosial Lokal - Jhon Kamaru; Rustam Tohopi; Yakob Noho Nani; Rusli Isa; Muchtar Ahmad (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study examines how administrative effectiveness shapes the implementation of social protection programs through a qualitative explanatory case study of the Program Keluarga Harapan (PKH) in rural Indonesia. While previous studies have primarily focused on program outcomes and policy design, limited attention has been given to the governance mechanisms through which administrative effectiveness influences implementation success. Drawing on Administrative Effectiveness Theory, this study analyzes four key governance mechanisms: targeting accuracy, program communication, goal attainment, and monitoring. Data were collected through in-depth interviews, field observations, and document analysis involving program implementers, beneficiaries, and local stakeholders. The data were analyzed using a process-tracing approach to identify the relationships between administrative processes and policy outcomes. The findings indicate that program effectiveness is not determined solely by the provision of cash transfers but by the interaction of administrative processes that connect policy objectives with beneficiary outcomes. Targeting accuracy enhances program legitimacy by ensuring assistance reaches eligible households, communication encourages behavioral compliance and program understanding, goal attainment is reflected in improved access to education and health services, while monitoring functions as an adaptive governance mechanism that facilitates continuous learning, accountability, and implementation adjustments. The study concludes that administrative effectiveness serves as an integrated governance mechanism linking state capacity, policy implementation, and social protection outcomes. These findings contribute to public administration literature by highlighting the importance of effective administrative governance in strengthening the sustainability and effectiveness of rural social protection programs.